2018
DOI: 10.1002/wps.20567
|View full text |Cite
|
Sign up to set email alerts
|

Management of common adverse effects of antipsychotic medications

Abstract: The benefits of antipsychotic medications are sometimes obscured by their adverse effects. These effects range from relatively minor tolerability issues (e.g., mild sedation or dry mouth) to very unpleasant (e.g., constipation, akathisia, sexual dysfunction) to painful (e.g., acute dystonias) to disfiguring (e.g., weight gain, tardive dyskinesia) to life-threatening (e.g., myocarditis, agranulocytosis). Importantly, adverse effect profiles are specific to each antipsychotic medication and do not neatly fit int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
205
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(263 citation statements)
references
References 245 publications
(250 reference statements)
6
205
0
10
Order By: Relevance
“…Finally, this meta‐review does not include data on strategies to prevent or mitigate adverse events of psychotropic medications in youth. While this is clearly an important area, this topic is beyond the scope of the present review and needs to be considered on the basis of targeted reviews and studies focusing on specific adverse events of individual medications 195‐201 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this meta‐review does not include data on strategies to prevent or mitigate adverse events of psychotropic medications in youth. While this is clearly an important area, this topic is beyond the scope of the present review and needs to be considered on the basis of targeted reviews and studies focusing on specific adverse events of individual medications 195‐201 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond causes seen in the general population, postural hypotension may be related to psychotropic medication, notably clozapine and quetiapine 200 . If increased fluid intake and salt consumption are ineffective, dose adjustment of switch of the responsible psychiatric medication should first be considered, followed by non-pharmacological therapy (appendix page 22: Table 3.6) with regular blood pressure monitoring.…”
Section: Postural Hypotensionmentioning
confidence: 99%
“…All TRAEs resolved without sequelae when the study drug was discontinued. The use of antipsychotics is associated with QTc prolongation, which can lead to life‐threatening arrhythmia . In this study with routine ECG assessment, only one atrioventricular block episode was reported in the haloperidol arm.…”
Section: Discussionmentioning
confidence: 60%